“Socially Conservative, But Politically Liberal:” A New Trend in Muslim Political Elites’ View in Indonesia - Aldi Nur Fadil Auliya (Jurnal Dialog, 2023)
A substantial amount of literature on conservative, liberal, and moderate views in Indonesia has been flooded with qualitative case studies. In contrast, this article discusses how Muslim political elites view Islam, democracy, and modernization in Indonesia by dichotomizing their socio-religious and political views divergently. Socio-religiously, it could be attributed to how they respond and practice their religious beliefs, such as prayer, performing five-time worship, reading the holy Qur'an, rejecting homosexuality, and interfaith marriage. Politically, it can be observed by how they respond to democratic citizenship equality, minority leadership, economic liberalism, Israeli-Palestinian issues, interfaith marriage rights, and the protection of LGBT. This article employed a qualitative study and conducted in-depth interviews with five Muslim political elites in Indonesia and consulted secondary data sources. In light of the convergence of Islam, democracy, and modernization, Muslim political elites in Indonesia hold a socially conservative but politically liberal viewpoint since they have to moderate their positions to please Islamic and nationalist voters within political liberalization. It causes them to rely not only on religious issues but also on good governance matters. This new trend in Muslim political elites’ views could impact people's perceptions by constructing a culture of liberal democratic models that are constantly changing and modifying, particularly in the Muslim world. This article could be beneficial for further research at the local and national levels or even be advanced to a quantitative study to contribute to the development of the modernization theory thesis in the Muslim world.